Performance analysis of reactive routing protocol based on less-flooding AODV and route stability aware in mobile ad-hoc networks - Roswan Ismail (2019)
The objective of this study is to propose a practical solution to help improve theperformance of the routing discovery process in Mobile Ad-hoc Networks(MANETs). The study involved the development of two new routing protocols,namely Less-Flooding Ad-hoc On-demand Distance Vector (LF-AODV) and RouteStability Aware (RSA) protocols, with the aim of reducing the number of transmittedroute request (RREQ) packets and link failures during the route discovery cycle.Accordingly, a series of simulations carried out with the NS-2 simulator to examinethe performance of such new protocols for 100 mobile nodes in an area measuring600 meters x 600 meters. The performance criteria were based on routing overhead(the total number of packets transmitted by a source node during the route discoveryprocess), average end-to-end delay (the average time taken by a packet to arrive at adestination node from a source node), and network lifetime (time taken until all nodesin a network die due to battery exhaustion). The simulation results showed that theRSA protocol managed to reduce the total overheads by 14% and 11%, and delays by29% and 21% with respect to the AODV and LF-AODV protocols, respectively.Furthermore, the RSA protocol was able to increase the network lifetime by 12% and8% compared to those of the AODV and LF-AODV protocols, respectively. Suchfindings suggest that the RSA protocol can help improve the performance ofMANETs by making such networks more stable and reliable. Clearly, such researchfindings will have a profound implication on the current practice of practitioners inthe network industry, notably service providers and mobile network operators, whocan use the RSA protocol to improve the quality of their products or services. Withthe use of more efficient, stable MANETs, end users will be able to use mobileapplications anywhere, anytime more reliably, resulting in higher user satisfaction thatbenefits all concerned.